PEMBERIAN HAK MILIK ATAS SATUAN RUMAH SUSUN BAGI WARGA NEGARA ASING DI INDONESIA - Lucy Karenina; Yoni Agus Setyono (The Juris, 2021)
The granting of property rights to flat units in Indonesia for foreign nationals is a legal reform in Indonesia that has many pros and cons. This study was conducted to describe the status of rights received by foreign citizens who wish to own an apartment unit in Indonesia and also the impact of the enactment of regulations for granting the status of ownership rights to flat units to foreign citizens in Indonesia. This study uses a normative juridical method. The conclusion in this study is that foreign citizens are given ownership rights to flat units on land with building rights or use rights on state land; or right to use building or right to use land with management rights. According to Law No. 11 of 2020 concerning Job Creation, Ownership rights to flat units are ownership rights to separate individual flat units with shared rights to shared parts, shared objects, and shared land. The positive impact of granting ownership rights to flat units to foreign nationals is the increase in foreign investment in Indonesia, advances in technology and human resources as well as increasing interest in doing business in Indonesia.